(untitled) - Timmons, Jeffry A. (Boston, 2009)
New Venture Creation: Entrepreneurship for the 21st Century is about the actual process of getting a new venture started, growing the venture, successfully harvesting it, and starting again. It continues to be the product of experience and considerable research in the field—rooted in real-world application and refined in the classroom. The design and flow of the book are aimed at creating knowledge, skills, and awareness. In a pragmatic way—through text, case studies and hands-on exercises—students are drawn in to discover critical aspects of entrepreneurship, and what levels of competencies, know-how, experience, attitudes, resources and networks are required to pursue different entrepreneurial opportunities. The Eighth edition includes new cases and exercises, updated Web sites, and new text material to capture the current financial, economic, technological, and globally competitive environment of this first decade of the new century.
Keywords: New business enterprises,Doanh nghiệp mới kinh doanh; Handbooks, manuals, etc, Sổ tay hướng dẫn v, hướng dẫn sử dụng, vv